Pro javaScript Development Coding, Capabilities, and Tolling - Odell, Den; Corrigan, Louise; Howdle, Ben; Inglis, Zach; SPi Global; Spi Global (New York Apress, 2014)
pro javascript Development is a practical guide for front-end web developers who are experienced at building web pages with HTML, CSS, and javaScript, and now wish to advance their JavaScript skills to a higher level. You will learn how to build large well-structured, high quality, mobile-optimeized web sites and apps, using the latest suppurted browser APls, language features, and tools. This book teaches and show you in practical hands-onterms how you scan.Master the performance, reliabiity, stability, and code manageability of your HavaScript. Understand and write efficient object-oriented and prototypal code, including full understanding of the "this" keyword. Boost the performance of your JavaSript code. Architect large web applications using common design patterns. Write high quality JavaScript code and avoid the pitfalls most likely to cause errors. Manage code dependencies with AMD and RequiresJS. Develop for mobile, build games, and set up a real-time video chat using modernPPls such as Geolocation, Canavas and WebRTC. Document your code as the professionals do. Write command-line and web server applications in JavaScript with Noode.js.Use build tools, such as Grunt and Gulp, to automate tasks and improve your development workflow. Using real-world examples and applications that you'll build yourself, pro JavaScript Development has unique, practical content that will make a better JavaScript developer. Become master of the latest JavaScript coding techniques and tools, and harness its best capabilities today
Content : Object-Oriented JavaScriipt -- Documting JavaScript -- Writing high-Quality JavaScriipt -- Boosting patterns, Creational, Structural, Begavioral and Architectural -- Mavaging code file dependencies -- Mobile JavaScript development -- Building games with Canvas API -- using webRTC for videw chat -- Using client-side templets -- The Node.js Application platform
"Books for professionals by professionals"
"The Expert's voice in web development"
Includes index
Intermediate to Advanced
12
NEW_ZAG_GN
Keywords: Computer Software; Computer games; Programming; Web Design; mobile programming; programming Languages